High-precision HD spectroscopy near 1.53 μm - Gotti, Riccardo; Wójtewicz, Szymon; Marangoni, Marco; Gatti, Davide; Lamperti, Marco (Frontiers in Physics, 2024)
We report highly precise and accurate measurements of the P(5), P(6) and O(3) transitions of the 2-0 band of HD occurring near 1.5 µm. HD spectra were acquired in the pressure range from 100 to 900 Torr with a cavity ring-down spectrometer linked to an optical frequency comb. The line-shape analysis was performed using the Hartmann-Tran profile in the so-called β-corrected version. For the P(5) transition we improve the accuracy of previous line center frequency determinations by more than two orders of magnitude. Moreover, for the P(5) and P(6) line centers the total standard uncertainty is below 3 MHz, similar to those provided by quantum electrodynamics predictions and thus useful for direct comparisons that might foster future improvements of the theoretical model.